A cohort study of maternal near-miss events and its adverse perinatal outcomes: an obstetrical finding in Northwest EthiopiaAJOG Global Reports at a Glance - Besfat Berihun Erega, BSc, MSc; Wassie Yazie Ferede, BSc, MSc (Elsevier, 2024)
BACKGROUND: Globally, various studies have reported that most adverse perinatal outcomes were associated with maternal near-misses. In Ethiopia, studies on adverse perinatal outcomes from maternal near-miss are scarce. OBJECTIVE: This study aimed to assess the incidence, determinants, and maternal near-miss effects on perinatal outcomes among women at public hospitals in the South Gondar zone in 2021. STUDY DESIGN: A facility-based prospective cohort study was conducted from January 10, 2021, to May 10, 2021. The chi-square test, multivariable logistic regression methods, and SPSS software were used. The strength of associations and significance level were examined using P values and odds ratios with 95% confidence intervals, respectively. In addition, multicollinearity and model fitness were checked. RESULTS: A total of 304 respondents (76 exposed and 228 unexposed) were included in the study with a response rate of 100.0%. The incidence rates of adverse perinatal outcomes among exposed and unexposed groups were 71.1% (95% confidence interval, 60.0-73.8) and 21.1% (95% confidence interval, 15.8-28.8), respectively. Multivariable logistic regression showed that short interbirth interval (adjusted odds ratio, 8.39; 95% confidence interval, 5.36-16.08), lower household income (adjusted odds ratio, 3.61; 95% confidence interval, 1.12-6.54), rural residence (adjusted odds ratio, 2.54; 95% confidence interval, 1.21-4.07), previous stillbirth (adjusted odds ratio, 4.24; 95% confidence interval, 1.04-17.31), absence of antenatal care (adjusted odds ratio, 9.84; 95% confidence interval, 4.89-17.51), and anemia (adjusted odds ratio, 4.19; 95% confidence interval, 1.01-17.46) were significantly associated with increased odds of adverse perinatal outcomes CONCLUSION: This study revealed that the incidence of adverse perinatal outcomes was significantly higher among exposed groups than unexposed groups. The result signified the need for improving the health of mothers by all stakeholders to improve perinatal outcomes.